Analysis of the four combination chemotherapies in non-small cell lung cancer treated at Maharaj Nakorn Chiang Mai Hospital - Thongprasert S. (2014)
From 1984 to 1991, patients with inoperable non-small cell lung cancer (NSCLC) were assigned to receive one of the four combination chemotherapies: 1. etoposide and cisplatin (P/VP-16), 2. vinblastine and cisplatin (P/V1b), 3. ifosfamide, epirubicin and cisplatin (IEP), 4. mitomycin, vinblastine and cisplatin (MVP). This study was not a randomized study, but it was a series of Phase II trials. The response rates were 11/29 (48.2%), 3/22 (13.6%), 18/40 (45%), 12/37 (32.4%), respectively. The response rate was significantly lower with the P/V1b regimen than with the P/VP-16, IEP or MVP (p = 0.04). The median survival times of responders were P/VP-16 11 months, IEP 12.4 months. Median survival time of MVP was 7+ months. For P/V1b survival time was not evaluated due to effect of secondary treatment. Since the response rate and survival duration of NSCLC patients treated with either one of these regimens were similar, the difference in view of drug toxicities and quality of life should be the most important issue concerning the selection of drug regimens in NSCLC.